Expert System For Diagnosing Pests And Diseases Of Ginger Plants Using Case-Based Reasoning Method - RIANA, FREZA; Laxmi, Gibtha; Djiwanti, Setyowati Retno; Harianingrum, Riska Pravita; Fajar Kusumah, Fitrah Satrya (Universitas Ibn Khladun Bogor, 2023)
Ginger (Zingiber officinale Rosc.) is a medicinal plant that has many benefits and properties that makes ginger one of the export commodities of Indonesian spices. One of the obstacles in exporting fresh ginger is the low quality of ginger caused by pest and disease attacks. Generally in preventing and controlling the spread of pests and diseases namely consult an expert, but the availability of experts is not always there in every area. Therefore this research builds a website based expert system to diagnose pests and diseases of ginger plants with the Case-Based Reasoning method. This method is a problem-solving that uses knowledge from previous experience to solve new problems. The expert system can diagnose five diseases and two pests with 39 symptoms. Based on the simulation test data as many as 50 done randomly, obtained a percentage value of 96% for expert diagnosis results with a system for the Case-Based Reasoning method. This Expert System can help farmers identify and control pests and diseases that attack the ginger plant.